2016
DOI: 10.15537/smj.2016.8.14822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dosages of oxycodone and fentanyl on the hemodynamic changes during intubation

Abstract: Objectives:To investigate the effectiveness of oxycodone compared with fentanyl for attenuating the hemodynamic response during endotracheal intubation.Methods:This study was conducted from June 2014 to February 2015 on healthy adults undergoing general anesthesia at the Yeungnam University Hospital, Daegu, Republic of Korea. Ninety-five patients were randomly assigned to one of 3 groups to receive the following drugs; Group F: fentanyl 2 µg/kg; Group O/70: oxycodone 140 µg/kg; Group O/100: oxycodone 200 µg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 19 publications
4
32
1
Order By: Relevance
“…In addition, oxycodone has much weaker μ‐receptor affinity than sufentanil, which may mitigate the adverse reactions related to μ‐receptor agonist, such as respiratory distress and the like, compared with sufentanil . A prospective, randomized, clinical trial suggested that the pretreatment of oxycodone could successfully attenuate the sympathetic response during the period of anesthetic induction . Therefore, it is of great importance to investigate the effects of oxycodone on anti–stress response, hemodynamics changes, respiration, and sedation during the preparation period of anesthesia and surgery for patients undergoing cardiac valve replacement.…”
mentioning
confidence: 99%
“…In addition, oxycodone has much weaker μ‐receptor affinity than sufentanil, which may mitigate the adverse reactions related to μ‐receptor agonist, such as respiratory distress and the like, compared with sufentanil . A prospective, randomized, clinical trial suggested that the pretreatment of oxycodone could successfully attenuate the sympathetic response during the period of anesthetic induction . Therefore, it is of great importance to investigate the effects of oxycodone on anti–stress response, hemodynamics changes, respiration, and sedation during the preparation period of anesthesia and surgery for patients undergoing cardiac valve replacement.…”
mentioning
confidence: 99%
“…Previous studies supported that oxycodone may offer advantages over fentanyl for pain control [9,10]. Recent data demonstrated that a lower dose of oxycodone was sufficient to control acute post-operative pain [22,23].…”
Section: Discussionmentioning
confidence: 97%
“…In recent decades, intravenous oxycodone has been used for perioperative pain management [7]. Comparing to morphine or fentanyl, intravenous oxycodone provides better pain relief, especially for visceral pain [8][9][10]. During induction of general anesthesia, previous studies have shown that the attenuation effect of oxycodone on hemodynamic responses is comparable to fentanyl, and the complication rates are also similar between these two opioids [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, fentanyl intravenous injection can cause the so called fentanyl-induced cough (FIC) during the induction, which may be explosive or even life-threatening (He et al, 2016;Park et al, 2016). It is particularly dangerous for those patients suffering from airway diseases, acute upper airway obstruction, cerebral aneurysm, increased intracranial pressure, brain trauma, brain hernia, or dissecting aortic aneurysm, as severe FIC could lead to pneumothorax, optic nerve injury, or rupture of aneurysms (Lim et al, 2013;Saleh et al, 2014;Firouzian et al, 2015;Park et al, 2016;Peringathara and Robinson, 2016). In clinical settings, the reported incidence of FIC is variable (18.0%-74.4%) depending on the dosage, infusion speed, and route of administration (Sedighinejad et al, 2013;Solanki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%